Clinical profile of lung cancer in Southern India with special reference to initial presentation and acceptance of treatment: A single-center study - Jat RR; Arumugam Velappan (Asian Journal of Medical Sciences, 2024)
Background: Lung cancer ranks as the second-most common cancer globally and remains the leading cause of cancer-related deaths. Despite a global decline in mortality due to reduced smoking, its incidence is rising in India. Aims and Objectives: This study retrospectively examines the clinical profiles of lung cancer patients at their initial presentation and treatment acceptance. Materials and Methods: This retrospective analysis used a database of 185 lung cancer patients reported at the Regional Cancer Centre, Tirunelveli, from January 2021 to December 2022. Clinical records of confirmed lung cancer cases were reviewed, focusing on demographic details, smoking history, symptoms, radiographic findings, histopathology, and clinical staging. Most patients underwent fiberoptic bronchoscopy or fine-needle aspiration biopsy. Patients were classified based on morphology and assessed using the modified Karnofsky Performance Scale and Eastern Cooperative Oncology Group (ECOG). Results: Most patients were male (74.5%), with a median age of 61 years. Most had an ECOG performance status of 0–2 (82.7%). Smoking was prevalent, with 53% of patients being current smokers. The most prominent symptoms at initial presentation were cough, dyspnea, fatigue, and weight loss. Adenocarcinoma was the predominant pathological type (47%). The right lung was more frequently affected, and most patients had comorbid conditions. Paclitaxel plus carboplatin was the primary first-line chemotherapy for most patients. A significant proportion (68.1%) were diagnosed at Stage IV, with the lung being the most common site of metastasis (46.8%). Conclusion: Most cases are diagnosed at advanced metastatic stages due to delayed diagnosis, often being initially misdiagnosed as tuberculosis.